MENINGKATKAN NILAI EKONOMIS SAMPAH MELALUI BANK SAMPAH PADA WARGA RW 04 KELURAHAN JATIHANDAP - Hani Hatimatunnisani; Riffka Fauzany; Fadil Habiburahman; Nita Rustanti (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M), 2025)
Household waste management remains a problem in several regions. Low public awareness of waste sorting is a contributing factor to increased environmental pollution and the loss of potential economic value. This study aims to analyze the role of waste banks in increasing the economic value of waste and encouraging the participation of RW 04 residents in community-based waste management. The research method used descriptive qualitative methods, with data collection techniques through observation, interviews, and documentation. The results indicate that the waste bank can increase additional income for residents of RW 04, especially housewives, reduce the volume of waste disposed of in the environment, and raise public awareness of sustainable waste management. Therefore, the existence of a waste bank is an effective strategic solution for waste management while simultaneously empowering the economic value of RW 04 residents.